Original paper Allergic risk zones of plane tree pollen (Platanus sp.) in Poznan - Nowak, Małgorzata; Szymańska, Agata; Grewling, Łukasz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction : Platanus is an ornamental tree commonly planted in the cities. In recent years the number of plane trees in Poznan has markedly increased. Because of the high allergenicity of plane tree pollen, the current tendency to plant a lot of young Platanus trees in Poznan seems to be disturbing. Aim: The main aim of this study was to prepare a map presenting zones of the highest allergic risk of plane tree pollen in Poznan. Material and methods: Daily average Platanus pollen counts (2005-2009) were collected in Poznan by two volumetric pollen traps located both in the city center and on the outskirts of Poznan. The field study of the distribution of Platanus trees in Poznan was conducted during three years (2008-2010). Results : The Platanus pollen season usually starts at the end of April and lasts for about 3 weeks. The highest pollen level was observed in the city center between 14.00 and 16.00 h. Trace quantities of pollen were detected on the outskirts of Poznan. Over 50 Platanus populations with a number of trees > 20 have been found mainly in the city center. The total number of specimens exceeded 1500, including 448 mature regularly flowering trees. Conclusions : Plane tree pollen exceeded the risk concentrations (> 50 P/m 3 ) only for few days, however during the intensive pollen season the pollen level can easily reach very high values. On the outskirts of Poznan, the pollen level is too low to induce allergic reactions. In recent years, over 1000 of new Platanus trees have been planted. Presumably, along with maturation of these young specimens, the exposure to plane pollen in the city will also increase.